Peran Moderator Ukuran Perusahaan dan Kualitas Audit dalam Hubungan Profitabilitas, Likuiditas, dan Nilai Perusahaan - Dewi, I Gusti Ayu Ratih Permata; Putri, Putu Yudha Asteria (Juara: Jurnal Riset Akuntansi, 2025)
The importance of firm value has made investors and creditors increasingly selective in investing in and extending credit to companies. Firm value is often used as a primary benchmark by investors and creditors because it reflects a comprehensive picture of a company's performance and prospects. Firm value can be influenced or determined by several factors, namely profitability and liquidity. The purpose of this study is to determine the effect of profitability and liquidity on firm value, as well as the moderating effects of firm size and audit quality in strengthening the relationship between profitability and liquidity on the value of companies listed on the Indonesia Stock Exchange during the 2021-2022 period. The sampling technique used was purposive sampling, with a total sample of 1,616. The data analysis technique used was moderated regression analysis with Stata software. The results show that profitability has no positive effect on firm value but liquidity has a positive effect on firm value. Firm size moderates liquidity on firm value, but does not moderate profitability on firm value. Conversely, audit quality moderates profitability and firm size on firm value. Investors and potential investors should pay attention to the information in financial reports, particularly regarding the company's value, to understand the company's true condition and use it as a basis for making informed and profitable investment decisions.